The effects of feed additive, selenium source, polyphenol, lysine level, and sow lactation feeder type on pigs - Rao, Zhong-Xing (Kansas State University, 2023)
Chapter 1 is a review paper that summarized the effects of 14 feed additive categories on grow-finish pig growth performance and carcass characteristics. The summarized data suggests that most results were positive for each feed additive; however, the magnitude of improvement varied, and most were not statistically significant. For ADG, DFM, Cu, L-carnitine, and multi-enzymes showed relatively large positive effects (> 2.1% improvement) across a reasonable number of articles. Acidifiers, betaine, CLA, multi-enzymes, DFM, L-carnitine, and yeasts showed relatively large positive effects (> 2.5% improvement) on improving G:F. Moreover, except for betaine, Cr, CLA, and L-carnitine, most feed additives showed little and non-significant effects on BF thickness (< 1.7% improvement). Chapter 2 utilized a total of 3,888 nursery pigs to evaluate selenium source on nursery pig growth performance, serum and tissue selenium concentrations, and serum antioxidant status. The results suggested that, compared to sodium selenite and selenium yeast, hydroxy-selenomethionine (OH-SeMet) had greater bioavailability as indicated by increased serum and tissue selenium concentration; however, antioxidant status was similar between treatments and OH-SeMet tended to reduce growth performance compared with pigs fed sodium selenite. Chapter 3 utilized a total of 300 nursery pigs to evaluate the effects of using polyphenols as a partial replacement for vitamin E in nursery pig diets. Increasing vitamin E equivalence improved feed efficiency which may be related to the improved antioxidant status. Providing additional vitamin E equivalence above the basal vitamin E requirement through either vitamin E or polyphenol showed similar benefits. Thus, the polyphenol used in this study can be used as an effective replacement for vitamin E supplemented above the basal requirement. Chapter 4 utilized a total of 702 90-kg finishing pigs to evaluate nutritional strategies for slowing growth rate then inducing compensatory growth. We found feeding Lys-restricted diets reduced the ADG and G:F of finishing pigs. Moreover, compensatory growth can be induced in Lys-restricted finishing pigs, but the duration of restriction and recovery influences the magnitude of compensatory growth. Chapter 5 utilized a total of 600 sows to evaluate sow feeder type and drip cooling on sow bodyweight, litter performance, and feeder cleaning criteria in a hot and humid environment. We determined that sows used SowMax feeders had reduced feed disappearance with no effects on sow and litter performance compared to a PVC tube feeder, and drip cooling improved sow and litter performance during summer in a hot and humid environment.
Keywords: Feed additive; Lysine level; Pig; Polyphenol; Selenium source; Sow lactation feeder